2012
DOI: 10.1242/jcs.109553
|View full text |Cite
|
Sign up to set email alerts
|

Anoctamins are a family of Ca2+ activated Cl− channels

Abstract: SummaryAnoctamin 1 (Ano1; TMEM16A) and anoctamin 2 (Ano2; TMEM16B) are novel Cl 2 channels transiently activated by an increase in intracellular Ca 2+. These channels are essential for epithelial Cl 2 secretion, smooth muscle peristalsis and olfactory signal transduction. They are central to inherited diseases and cancer and can act as heat sensors. Surprisingly, another member of this protein family, Ano6, operates as a Ca 2+ -activated phospholipid scramblase, and others were reported as intracellular protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
182
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(202 citation statements)
references
References 40 publications
20
182
0
Order By: Relevance
“…Szteyn et al (33) reported that endogenous TMEM16F functions as a CaCC in mouse dendritic cells on the basis of siRNA-mediated knockdown. Tian et al (34) also recently reported that Cl Ϫ current activation was induced in human TMEM16F-overexpressing HEK293 cells when the intracellular Ca 2ϩ concentration was increased to more than 10 M. These observations are in agreement with our present study. In contrast, Yang et al (36) reported that TMEM16F forms a Ca 2ϩ -activated cation channel based on the data obtained by knockout mice and heterologous expression.…”
Section: Note Added In Proofsupporting
confidence: 94%
“…Szteyn et al (33) reported that endogenous TMEM16F functions as a CaCC in mouse dendritic cells on the basis of siRNA-mediated knockdown. Tian et al (34) also recently reported that Cl Ϫ current activation was induced in human TMEM16F-overexpressing HEK293 cells when the intracellular Ca 2ϩ concentration was increased to more than 10 M. These observations are in agreement with our present study. In contrast, Yang et al (36) reported that TMEM16F forms a Ca 2ϩ -activated cation channel based on the data obtained by knockout mice and heterologous expression.…”
Section: Note Added In Proofsupporting
confidence: 94%
“…These results came as a surprise, since Ano6 has been characterized as a Ca 2þ -activated Cl 2 channel. Moreover, Ca 2þ -activated Cl 2 currents were also observed after overexpression of Ano4, 7 and 9 [6,55,56,61,62]. However, Cl 2 channel and scramblase activity were shown to be independent [55].…”
Section: Other Anoctamins Correlated To Cancermentioning
confidence: 95%
“…However, their molecular identity remained elusive until 2008, when three groups independently cloned the gene encoding the transmembrane protein called TMEM16A or anoctamin-1 (ANO1) (5,33,46). This protein was observed to function as a Ca 2ϩ -activated chloride channel (26,37) and to be widely expressed at the plasma membrane of many cells in liver, skeletal muscle, heart, pancreas, placenta, sensory neurons, kidney, airways epithelial cells, lung alveoli, and mammary and salivary glands where they concentrate at the apical membrane (8). The functional properties of ANO1 were found to be regulated by alternative splicing and some variants were observed to be expressed in the thyroid (9).…”
mentioning
confidence: 99%